﻿﻿﻿Outcome of patients with interstitial lung disease admitted to the intensive care unit - ﻿﻿Vial-Dupuy, A.; ﻿﻿﻿Sanchez, O.; ﻿﻿Douvry, B.; Guetta, L.; Juvin, K.; Wermert, D.; Guérot, E.; Israël-Biet, D. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Introduction: The outcome of acute respiratory failure (ARF) affecting patients with various interstitial lung diseases (ILD) is poorly defined particularly in those with drug-induced ILD (DI-ILD). We investigated this issue focusing on fibrosing idiopathic interstitial pneumonitis (FIIP) and DI-ILD. Methods: We carried out a retrospective study of patients with ILD admitted in a single center ICU. The primary end-point was in-hospital mortality. Results: We included 72 subjects who fell into 3 diagnostic groups: DI-ILD (n=20), FIIP (n=28) and miscellaneous (M-ILD) (n=24). In-hospital mortality rates were 40% (n=8/20), 68% (n=19/28), and 25% (n=6/24) for DI-ILD, FIIP and M-ILD, respectively, (p=0.006). It reached, 64% (n=7/11), 100% (n=17/17) and 60% (n=6/10), respectively, in subjects on mechanical ventilation (p=0.007). In multivariate analysis, the need for mechanical ventilation (OR= 35; [95% CI, 5-255]), the type of ILD (FIIP vs miscellaneous) (OR=22; [95% CI, 3-147]) and high-dose steroids during ICU stay (OR=0.19; [95% CI, 0.04-0.99]) were independent determinants of in-hospital mortality. Conclusion: This study, while confirming the poor prognosis of FIIP patients in ICU, highlights the better prognosis of DI-ILD and M-ILD even though severity criteria on admission are similar in these 3 groups. These data impact on the management of these patients in ICU in whom a proper diagnostic of the underlying condition is crucial.